Propostas teórico-metodológicas do ENEM: relações entre o enfoque CTS/CTSA e o discurso de professores acerca da prática docente - Alves, Alini Roberta (2011)
This work falls within the field of science teaching aimed at the Brazilian high school and want to investigate some of its relations with an evaluation model, specifically the National Secondary Education Examination (Enem); aiming thus, conduct a study of this examination and discourse of practice teachers in a public school School of São Carlos (SP) of this assessment, based on theoretical assumptions of the STS / STSE for believing that there are close relations that can be woven between these dimensions. As such, there is a documentary analysis of the proposal and proof of Natural Sciences and Technologies and its held focus groups and semi-structured interviews with teachers of high school to a state school in San Carlos, basing on the methodology qualitative analysis, with emphasis on content analysis. In document analysis skills and abilities were observed subtle approaches to STS / CTSA, particularly with regard to the ambivalence of scientific and technological development. The test analysis of natural sciences and their technologies in 2009, also showed shallow approaches to STS / CTSA, since 60% of the questions the aspects of science were not treated with any reasonable dimensions and influences. The context was used in most of the time, as an illustration and not for transformation a reality, and interdisciplinarity was absent in 60% of the questions basically. According to the results found in teaching discourse, evidence of the Enem emphasize social and environmental issues, science is treated as charged content, and technology in specific moments. Furthermore, teachers believe that the context and the interdisciplinary, often show themselves to unnecessary. Moreover, in their speech, there was appreciation of the Enem after its change, which occurred in 2009, the frequent use of examination questions in the classroom as well as the change in focus from teachers to treat the Enem. Regarding the presence of STS / STSE, they emphasized the importance both in the classroom - to bring a broader view of events - and in the evaluations as Enem for not only enhance the application of scientific content.